Determination of Heavy Metal Contaminations of Lead and Cadmium in Selected Lipstick Products Sold in Padang City Using Atomic Absorption Spectrophotometry - Rusdi; Robi Budi Yandra; Nessa; Ridho Asra (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
The study was aimed at assessing the levels of some toxic metals of lead and cadmium in selected lipstick products sold in Padang city. Four brands of lipsticks were taken which were BL, NK, PS and WD. The lipsticks were grinded and analyzed for heavy metals (lead and cadmium) using atomic absorption spectrophotometry. Each sample was destructed by nitric acid and perchloric acid (3:1). Destructed samples were added with sodium hydroxide to liberate ammonia and filtered into a 25 mL volumetric flask. The concentrations of heavy metal were measured by using atomic absorption spectrophotometry. The results showed that lead heavy metal contamination was not detected. Whereas, the heavy metal contamination of cadmium in lipstick brands BL, NK, PS and WD were 0.2287, 0.2000, 0.1796 and 0.1220 mg/kg, respectively. The study results showed that all metal contaminations of lead and cadmium were not over the limit which were regulated by National Agency of Drug and Food Control of the Republic of Indonesia.